Time delay in photoionization of half-filled shell atoms. (August 2015) - Dolmatov, V K; Kheifets, A S; Manson, S T; Deshmukh, P C
Synopsis: Time delay in photoionization of a half-filled shell atom is predicted to be strongly term-dependent and subject to the dramatic impact of a giant autoionization resonance. Photoionization of the Mn atom is chosen as a case study.